2022
DOI: 10.36834/cmej.73058
|View full text |Cite
|
Sign up to set email alerts
|

When patients teach students empathy: a systematic review of interventions for promoting medical student empathy

Abstract: Background: Despite growing emphasis on empathic care, numerous studies demonstrate diminishing empathy in medical students. Involving patient educators in medical curricula may be a solution. Therefore, we conducted a systematic review to evaluate patient-involved interventions that promote empathy among medical students.  Method: A literature search of MEDLINE, Embase, PsycINFO, and ERIC databases was performed using the keywords “empathy,” “medical student,” and their synonyms. Results were independently sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…Our participants agreed that clinical empathy should be an essential component of medical school training and suggested increasing patient involvement in medical education, a strategy that was shown to enhance student empathy and knowledge in a recent systematic review. 16 Our participants also suggested that admission of more students with personal illness experiences may foster better understanding of patients with chronic illness. 43 , 44 Currently, medical students with chronic illness and disability are frequently undersupported and excluded from medical training.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our participants agreed that clinical empathy should be an essential component of medical school training and suggested increasing patient involvement in medical education, a strategy that was shown to enhance student empathy and knowledge in a recent systematic review. 16 Our participants also suggested that admission of more students with personal illness experiences may foster better understanding of patients with chronic illness. 43 , 44 Currently, medical students with chronic illness and disability are frequently undersupported and excluded from medical training.…”
Section: Discussionmentioning
confidence: 89%
“…Patient partnerships are increasingly recognized as central to designing health care interventions, and already feature prominently in research design, health policy and medical education in other countries. 16 , 18 , 19 Studies examining patient experiences of clinical empathy have also been primarily restricted to specific illness contexts. 20 22 However, we hypothesize that patients’ experiences of clinical empathy are not unique to particular diagnoses and that it is these universal factors that are the most useful in informing undergraduate medical education, since they are relevant to all future clinicians.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of how to emphasize these motivational factors could be in tailoring curricula: formal (what to teach with empathy), informal (how to improve learning environments), and hidden (addressing factors that overwhelm students, such as workload) [ 2 , 31 ]. Our findings may also help guide interventions that cultivate medical student empathy through autonomy-supportive SDT principles – for instance, in workshops for medical teachers on how to support medical learners’ basic psychological needs [ 31 ], and sessions for medical students on how to support patient autonomy, coupled with patient feedback [ 43 ]. Regardless of whether a medical student is ‘high’ or ‘low’ in self-determination, we would do well to create psychological safety for them, foster their self-awareness, and help them recognize choices in when and how to be empathic with patients.…”
Section: Discussionmentioning
confidence: 99%
“…When patients teach students empathy: a systematic review of interventions for promoting medical student empathy by Boshra and team 22 studied existing patient-involved interventions to improve empathy among medical students. The authors found that patient-led education positively impacted medical student empathy and increased their understanding of the subject.…”
Section: Discussionmentioning
confidence: 99%